Blocking NF-κB nuclear translocation leads to p53-related autophagy activation and cell apoptosis - Zhu, Bao-Song (Baishideng Publishing Group Co., Limited, 2011)
AIM: To investigate the anti-tumor effects of nuclear factor-κB (NF-κB) inhibitor SN50 and related mechanisms of SGC7901 human gastric carcinoma cells. METHODS: MTT assay was used to determine the cytotoxic effects of SN50 in gastric cancer cell line SGC7901. Hoechst 33258 staining was used to detect apoptosis morphological changes after SN50 treatment. Activation of autophagy was monitored with monodansylcadaverine (MDC) staining after SN50 treatment.Immunofluorescence staining was used to detect the expression of light chain 3 (LC3). Mitochondrial membrane potential was measured using the fluorescent probe JC-1. Western blotting analysis were used to determine the expression of proteins involved in apoptosis and autophagy including p53, p53 upregulated modulator of apoptosis (PUMA), damage-regulated autophagy modulator (DRAM), LC3 and Beclin 1. We detected the effects of p53-mediated autophagy activation on the apoptosis of SGC7901 cells with the p53 inhibitor pifithrin-α. RESULTS: The viability of SGC7901 cells was inhibited after SN50 treatment. Inductions in the expression of apoptotic protein p53 and PUMA as well as autophagic protein DRAM, LC3 and Beclin 1 were detected with Western blotting analysis. SN50-treated cells exhibited punctuate microtubule-associated protein 1 LC3 in immunoreactivity and MDC-labeled vesicles increased after treatment of SN50 by MDC staining. Collapse of mitochondrial membrane potential Δψ were detected for 6 to 24 h after SN50 treatment. SN50-induced increases in PUMA, DRAM, LC3 and Beclin 1 and cell death were blocked by the p53 specific inhibitor pifithrin-α. CONCLUSION: The anti-tumor activity of NF-κB inhibitors is associated with p53-mediated activation of autophagy.